2016
DOI: 10.1007/s00345-016-1840-4
|View full text |Cite
|
Sign up to set email alerts
|

Robot-assisted ureteral reconstruction using a tubularized peritoneal flap: a novel technique in a chronic porcine model

Abstract: Robot-assisted ureteral reconstruction using a tubularized peritoneum flap is technically feasible and reproducible. The flap sustained abundant vascular supply after different intervals of follow-up and the peritoneal mesenchymal cells differentiated into urothelium and myofibroblasts. Further studies are needed to address the issue of functional obstruction to improve long-term renal function outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…After 10 weeks, histological examination showed that the constructed ureteral lumens were lined with transitional epithelium. Brandao et al 22 performed robotic ureteral reconstruction with a tubularized peritoneal flap in six pigs and reported focal urothelial lining of the neoureter. In our study, we removed the entire bladder and replaced it with a neobladder assembled from the peritoneal sheet and the seromuscular layer of the ileum.…”
Section: Discussionmentioning
confidence: 99%
“…After 10 weeks, histological examination showed that the constructed ureteral lumens were lined with transitional epithelium. Brandao et al 22 performed robotic ureteral reconstruction with a tubularized peritoneal flap in six pigs and reported focal urothelial lining of the neoureter. In our study, we removed the entire bladder and replaced it with a neobladder assembled from the peritoneal sheet and the seromuscular layer of the ileum.…”
Section: Discussionmentioning
confidence: 99%
“…In an interesting article, Brandao et al . reported the use of a tubularized peritoneal flap to bridge an artificially‐created ureteral defect in an animal model . Although they reported technical feasibility, they noted significant shrinkage in the length and width of the flap.…”
mentioning
confidence: 99%